Determinants of Tax Compliance in Windhoek Namibia - Iileka, Wilkka Natangwe; Jeke, Leward; Muleya, Henry; Manenge, Robson; Abel, Sanderson (International Journal of Economics and Financial Issues, 2026)
Taxation is a complex area for many taxpayers since tax laws are often difficult to interpret. This means most taxpayers lack sufficient knowledge to correctly treat specific income items for tax purposes hence the face the challenge of noncompliance. The study sought to investigate the determinants of tax compliance in Windhoek. The study used a mixed research approach. The population of the study comprised of Windhoek residence. Using an on-line survey with questionnaires, a sample of 89 taxpayers was accessed. The results revealed that the majority of taxpayers were not tax compliant. It also revealed that tax rate, tax audit, government spending, personal financial constraints, awareness on offences, penalty rate, tax knowledge, fairness and government policy are significant factors affecting tax compliance. Finally, the study recommended that the Namibian government should establish an institution to educate ordinary citizens on issues pertaining to tax compliance and all associated policies related to taxation.